2023
DOI: 10.48084/etasr.6335
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia Detection in Chest X-Rays using Transfer Learning and TPUs

Niranjan C. Kundur,
Bellary Chiterki Anil,
Praveen M. Dhulavvagol
et al.

Abstract: Pneumonia is a severe respiratory disease with potentially life-threatening consequences if not promptly diagnosed and treated. Chest X-rays are commonly employed for pneumonia detection, but interpreting the images can pose challenges. This study explores the efficacy of four popular transfer learning models, namely VGG16, ResNet, InceptionNet, and DenseNet, alongside a custom CNN model for this task. The model performance is evaluated using Mean Absolute Error (MAE) as the performance metric. The findings re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…While this study demonstrated machine learning's potential in medical imaging, its limitations lie in the necessity for extensive data augmentation to balance the dataset and optimize feature extraction, which can be resource-intensive and may not scale well in different clinical environments. The authors [24] delved into the utility of several advanced image recognition models to improve pneumonia detection from chest X-rays. This investigation deployed models like VGG16, ResNet, InceptionNet, and DenseNet, as well as a tailored CNN model.…”
Section: Related Workmentioning
confidence: 99%
“…While this study demonstrated machine learning's potential in medical imaging, its limitations lie in the necessity for extensive data augmentation to balance the dataset and optimize feature extraction, which can be resource-intensive and may not scale well in different clinical environments. The authors [24] delved into the utility of several advanced image recognition models to improve pneumonia detection from chest X-rays. This investigation deployed models like VGG16, ResNet, InceptionNet, and DenseNet, as well as a tailored CNN model.…”
Section: Related Workmentioning
confidence: 99%
“…Image segmentation of dental works is essential for proper patient treatment since there are various objects a medical practitioner would observe through this process, which would facilitate the former to successfully deal with the patient's issue. This study deploys the periapical view of the tooth from the detailed X-rays [5,6]. The aforementioned objects have been generalized into three main classes, namely Endodontic, Restoration, and Implant.…”
Section: Introductionmentioning
confidence: 99%
“…An algorithm based on Dynamic Voltage Frequency Scaling (DVFS) [3,4], is implemented to explore the characteristics confined to frame controlled rendering GPUs and reach desirable power savings. The workload of each frame is analyzed in the 3D scene by considering factors such as geometry [5,6], textures, pixels [7], and rasterization. This analysis helps in understanding computational intensity of each frame.…”
Section: Introductionmentioning
confidence: 99%